x=-3
Chat with our AI personalities
If: 5x = 4x+7 Then: 5x-4x = 7 And: x = 7
5x+3y = 51 y = 10x-8 Substituting the bottom equation into the top equation: 5x+3(10x-8) = 51 5x+30x-24 = 51 5x+30x = 51+24 35x = 75 Divide both sides by 35 to find the value of x: x = 75/35 = 15/7 in its lowest terms. Substitute the value of x into the original equations to find the value of y: So: x = 15/7 and y = 94/7
It is 56-10x
The 7x and the 5x are like terms. This means that you can add them up. Think about it, 7 x's plus 5x's equals 12x's. From there, you can divide 12 from both sides of the equation, and you will get that x = 2.
4x - 3 - 5x + 7 = 6 4x - 5x = 3 - 7 + 6 -1x = 2 x = -2